Please help! Question is given below in form of image!

Answer:
None of the choices are correct.
Step-by-step explanation:
[tex] 9x^3 + 9x^2 - 4x - 4 = 0 [/tex]
The polynomial has 4 terms and no common factors. We can try factoring by grouping.
[tex] 9x^2(x + 1) - 4(x + 1) = 0 [/tex]
[tex] (x + 1)(9x^2 - 4) = 0 [/tex]
Now we factor the difference of squares.
[tex] (x + 1)(3x + 2)(3x - 2) = 0 [/tex]
[tex] x + 1 = 0~~or~~3x + 2 = 0~~or~~3x - 2 = 0 [/tex]
[tex]x = -1~~or~~x = -\dfrac{2}{3}~~or~~x = \dfrac{2}{3}[/tex]
None of the choices are correct.